Climate Change and Writing the Canadian Arctic - Hulan, Renée (Springer International Publishing, 2018)
Climate Change and Writing the Canadian Arctic explores the impact of climate change on Canadian literary culture. Analysis of the changing rhetoric surrounding the discovery of the lost ships of the Franklin expedition serves to highlight the political and economic interests that have historically motivated Canada's approach to the Arctic and shaped literary representations. A recent shift in Canadian writing away from national sovereignty to circumpolar stewardship is revealed in detailed close readings of Kathleen Winter's Boundless and Sheila Watt-Cloutier's The Right to Be Cold. .